1997
DOI: 10.1098/rspb.1997.0057
|View full text |Cite
|
Sign up to set email alerts
|

Variation in extinction risk among birds: chance or evolutionary predisposition?

Abstract: SUMMARY Collar et al. (1994) estimate that of the 9672 extant species of bird, 1111 are threatened by extinction. Here, we test whether these threatened species are simply a random sample of birds, or whether there is something about their biology that predisposes them to extinction. We ask three specific questions. First, is extinction risk randomly distributed among families ? Second, which families, if any, contain more, or less, threatened species than would be expected by chance ? Third, is variation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
391
4
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 394 publications
(426 citation statements)
references
References 22 publications
18
391
4
2
Order By: Relevance
“…There does seem to be a general trend within some clades for threatened species to be overrepresented in speciespoor clades (e.g. in mammals, Purvis et al 2000b andbirds, Bennett andOwens 1997 ). In plants, patterns appear mixed.…”
Section: Quantifying the Loss Of Evolutionary Historymentioning
confidence: 95%
See 4 more Smart Citations
“…There does seem to be a general trend within some clades for threatened species to be overrepresented in speciespoor clades (e.g. in mammals, Purvis et al 2000b andbirds, Bennett andOwens 1997 ). In plants, patterns appear mixed.…”
Section: Quantifying the Loss Of Evolutionary Historymentioning
confidence: 95%
“…If closely related species also tend to have close geographical proximities, perhaps refl ecting shared habitat preferences or the geographical process of speciation, they will then also be exposed to similar intensity of extinction drivers. There is an increasing weight of evidence suggesting that extinction risk is generally more clustered on a phylogeny than expected by chance (Bennett and Owens 1997 ;Purvis et al 2000a ;Schwartz and Simberloff 2001 ), a pattern also observed within the fossil record. Extinction will thus prune the tree-of-life non-randomly.…”
Section: Phylogenetic Structure In Extinction Risksmentioning
confidence: 98%
See 3 more Smart Citations